The industrial anaerobe Clostridium acetobutylicum uses polyketides to regulate cellular differentiation - Nicolaus A. Herman (Nature Portfolio, 2017)
Polyketides are secondary metabolites mainly found in aerobic organisms with wide applications in medicine and agriculture. Here, the authors uncover new polyketides native to the anaerobic bacterium Clostridium acetobutylicum and show their role in triggering sporulation and granulose accumulation.